Development of Learning Management System and Its Effect in Students’ Academic Performance - Josan D. Tamayo (Future Science / FSH-PH Publications, 2025)
Technology in the educational institution enhances the teaching and learning experiences of both teachers and students. Learning Management System is a technological advancement which has been adopted by several institutions. Not only it helped in delivering online teaching materials but served as a way of communication. This study aimed to develop and validate a rule-based adaptive LMS using the ADDIE model and determine its influence on students’ academic performance. Results showed that regression and correlation analysis identified time spent in LMS (r = +.812) and time spent viewing pages (r = +.877) as statistically significant predictors of academic performance, whereas login frequency (r = –.065) showed negligible effect. Expert and user evaluation rated the system at a “great extent,” with subject matter content, instructional design, and software evaluation emerging as key factors affecting LMS acceptability. Findings suggest that sustained engagement and quality content drive improved performance.